Structures and dynamics of optically confined matter - Dear, R; R D Dear (2013)
This thesis explores the structures and dynamics of optically confined matter, ranging from single particle traps to complex optically bound colloidal arrays, investigating and quantifying the behaviour of each system. It begins with an introduction to optical manipulation techniques and a discussion of the development of the single beam gradient force trap, more commonly referred to as optical tweezers. Following this, the building of a single beam optical trap will be presented alongside a discussion of some of the key components in such a setup, before it is calibrated, allowing a demonstration of some of the techniques which are utilised later in the thesis. The optical trapping of aerosol droplets is an area of key importance in atmospheric chemistry, as optical tweezers provide a valuable and versatile tool for droplet manipulation and characterisation. Trapping single aerosol droplets is facilitated by using annular rather than conventional Gaussian beams, as will be demonstrated, with significant advantages in increasing the size range of trappable droplets, and improving their axial localisation. These improvements will be demonstrated experimentally with an in-depth comparison of Gaussian and annular beam trapping. These enhancements are also verified theoretically using a model developed by Burnham and McGloin, showing excellent agreement with experimental results. Ionic liquids, defined as organic salts with melting points below room temperature, are another area of great contemporary interest. They are highly tunable and so have been referred to as "designer solvents", and also have important applications as "green" solvents in organic chemistry. Trapping particles within these novel liquids allows a micro-rheological investigation of their properties to be conducted. This is demonstrated by determining the temperature dependent viscosity changes of these media, showing excellent agreement with previous macro-rheological studies. In addition, hydrodynamic effects such as Faxen's correction to viscous drag in proximity to a surface, and hydrodynamic coupling between pairs of colloids trapped in ionic liquids are demonstrated. Following these single and dual particle studies, this thesis continues with an investigation of the structures and dynamics of optically bound matter formed of larger numbers of particles. The behaviour of these optically bound structures is particularly sensitive to the number of particles involved, and so a counter-propagating evanescent field trap in conjunction with an inverted optical tweezers setup is utilised in order to controllably assemble these structures and study the factors affecting their behaviour. Initially one-dimensional chains of optically bound 3.5 um diameter silica particles are studied, allowing an implementation of Generalized Lorentz-Mie Theory (GLMT) to be developed through collaboration with Dr. Jonathan Taylor of The University of Glasgow. Experimental and theoretical insights allow further understanding of the processes involved in the formation of these structures. Having studied the behaviour of 3.5 um diameter silica particles in a counter-propagating evanescent wave trap, the effects of changing particle size and refractive index are presented by using smaller silica and melamine particles. These results are explained in terms of the increased importance of interference fringes in determining the arrangement of the optically bound structures of smaller particles, and due to the increased interaction of the melamine particles with the evanescent field as a result of the larger refractive index contrast between them and the trapping medium. The thesis then concludes with a study of the dynamics of the previously presented optically bound chains. Initially the diffusion of single particles in the evanescent field is compared to their freely-diffusing behaviour, quantifying the confining effect of the field. The addition of particles to the field then allows the diffusive behaviour to be studied as a function of particle number, and understood in terms of on-axis confinement by adjacent particles. The tilting of these optically bound chains relative to the inter-beam axis is also explored as a function of particle number, as is the rigidity of these chains. Finally a more complex, dynamic effect is presented, dubbed "Newton's Cradle", in which particles are ejected from the ends of the chains before returning and repeating this process. This behaviour is understood by utilising the previously developed GLMT simulations.